Horace's "Odes" - Tarrant, R. J. 1945- (Oxford approaches to classical literature, 2020)
Horace's body of lyric poetry, the Odes, is one of the greatest achievements of Latin literature and a foundational text for the Western poetic tradition. These 103 exquisitely crafted poems speak in a distinctive voice - usually detached, often ironic, always humane - reflecting on the changing Roman world that Horace lived in and also on more universal themes of friendship, love, and mortality. This text introduces readers to the Odes by situating them in the context of Horace's career as a poet and by defining their relationship to earlier literature, Greek and Roman. Several poems have been freshly translated by the author; others appear in versions by Horace's best modern translators